Thriving social network for communication on elearning: exploring gender differences in attitudes - Vate-U-Lan, Poonsri; Masouras, Panicos (My University, 2018)
ACM The main objective of this study was to survey online students' attitudes towards communication for eLearning on social network sites. This online survey resulted in 896 valid responses. The statistics for interpreting were percentage, mean, standard deviation, t-test independent and one-way ANOVA. The average score of the attitude towards using eLearning on social network site was positive (4.23 out of 6, SD=1.10). The findings confirmed that the most popular among social network sites was Facebook. It also found a statistically significant difference between genders' attitude, where by the female attitude scored higher than male, and both being positive. The highest attitude earned from the survey concluding students believed that social networks support eLearning potential (4.31 out of 6, SD=1.30). There was a statistically significant difference in attitude for participants who had varied experiences using eLearning. Participants who were experienced in both formal and informal eLearning showed a higher attitude towards eLearning on social network sites as opposed to participants who used informal eLearning only.
Keywords: Attitude; Communication; ELearning; Facebook; Learning Management Systems (LMS); Social Network